2011
DOI: 10.1007/s11859-011-0707-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and thermodynamic properties of BaS: An Ab initio study

Abstract: The hydrostatic-pressure-induced transition phase of BaS from the NaCl-type structure (B1) to the CsCl-type structure (B2) is investigated by ab initio plane-wave pseudopotential density functional theory method. It is found that the transition pressure from B1 to B2 phases is 8.2 GPa according to the usual condition of equal enthalpy. Through the quasi-harmonic Debye model, the dependences of the relative volume V/V 0 on the pressure P, the thermal expansion parameter ratio 0 0 ( )/ γ γ γ − on pressure P, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…1c). Both BaS modifications were optimized using first principles calculations with LDA and GGA, and the results were in a very good agreement with previous experimental [17][18][19][20][21][22]24] and theoretical results [11,12,23,[25][26][27][28][29][30]47,48]. Since it has been observed that the calculated values of the cell parameters were slightly underestimated compared to the experimental values, while the GGA-PBE functional slightly overestimates (see supporting information, Table S1), each of the investigated properties in this study were calculated with both LDA and GGA approaches for comparison.…”
Section: Structural Changes Of Bas At High Pressuresupporting
confidence: 81%
See 1 more Smart Citation
“…1c). Both BaS modifications were optimized using first principles calculations with LDA and GGA, and the results were in a very good agreement with previous experimental [17][18][19][20][21][22]24] and theoretical results [11,12,23,[25][26][27][28][29][30]47,48]. Since it has been observed that the calculated values of the cell parameters were slightly underestimated compared to the experimental values, while the GGA-PBE functional slightly overestimates (see supporting information, Table S1), each of the investigated properties in this study were calculated with both LDA and GGA approaches for comparison.…”
Section: Structural Changes Of Bas At High Pressuresupporting
confidence: 81%
“…There has been extensive theoretical work published on barium sulphide in the literature, mostly because of opto-electrical applications of barium chalcogenides. Most of these researches are focusing on the phase transitions, band structure, density of states (DOS), thermodynamic and elastic properties of well-known NaCl and CsCl modifications at standard conditions [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Grüneisen parameter γ is another important thermodynamic quantity which is thought to be described as the alteration in a frequency of the crystal lattice vibration based on the lattice's increase or decrease in volume as the temperature changes [48]. The Grüneisen parameter of cubic NbFeSb is presented in figure 9 under various pressures and temperatures.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…These research results have played an important role in promoting the safety evaluation of ship lock operation, but due to many factors affecting the safety of ship lock operation and the work to be done, there is no relevant and complete safety evaluation system around the world (Teng 2011).…”
Section: Literature Reviewmentioning
confidence: 99%